Spontaneous umbilical hernia rupture with omental evisceration and Flood syndrome - Colbran, Rachel; Smith, Alison; Melloy, Aemelia; Iyer, Ramesh (International Surgery Journal, 2019)
Cirrhotic patients are at increased risk of developing umbilical hernias. Many cirrhotic patients’ umbilical hernias are not repaired electively due to concerns for high perioperative morbidity and mortality. This case report aims to inform clinicians about the unique challenges that arise during emergency management of umbilical hernias in the cirrhotic patient. A 59-year-old male with Child-Turcotte-Pugh grade B cirrhosis presented to our hospital with an incarcerated umbilical hernia that spontaneously ruptured with large volume ascitic leak (known as Flood syndrome) and omental evisceration. The patient underwent emergency sutured umbilical hernia repair, and required a prolonged post-operative stay in the hospital intensive care unit after suffering from complications including spontaneous bacterial peritonitis, anaphylaxis to antibiotic treatment, aspiration pneumonia, encephalopathy and worsening ascites. He eventually made a good recovery and underwent rehabilitation prior to discharge home. This case highlights the rare complication of spontaneous omental evisceration of an umbilical hernia in the cirrhotic patient and details its subsequent management. It is important to note that elective hernia repair after medical optimisation is high risk in the cirrhotic patient, but is recommended to avoid the high perioperative mortality and morbidity associated with emergency repair.